Methods for neuroimaging with ultra high field MRI - Aphiwatthanasumet, Kingkarn (2019)
This work is focused on developing methods for neuroimaging in vivo at 7.0 T with high resolution and high contrast in a reasonable scanning time. The methods optimised here have been tested in various brain regions, in small cohorts, in both health and disease, including a consideration of the usefulness and pitfalls of high field MRI.